Students\' Knowledge and Attitude of Hygiene and Food Safety at Shahid Sadoughi University of Medical Sciences in Yazd, Iran - Hadi Eslami; Ameneh Marzban; Fateme AkramiMohajeri; Zeynab Rezaei; Mohammad Rafati Fard (Shahid Sadoughi University of Medical Sciences, 2015)
Introduction: Today, transmitted diseases through food and food poisoning have been considered as a public health problem in many countries. Lack of knowledge concerning hygiene and food safety can increase the risks associated with the consumed foods. Hence, the present study aimed to determine the students' knowledge and attitude of hygiene and food safety in Shahid Sadoughi University of Medical Sciences in Yazd. Materials & Methods: This study is a cross-sectional survey in which 358 students were selected, out of 5400 students of different Schools of Shahid Sadoughi University of Medical Sciences in Yazd, via stratified random sampling method. In order to glean the study data, a questionnaire was applied, which were then analyzed applying Mann- Whitney and Kruskal-Wallis tests. Results: The mean score of knowledge has been reported in a low level within 33% of students and the mean score of attitude has been demonstrated to be at a good level within 63.4% of students. Most students revealed a low knowledge level regarding the proper procedures for food storage and food-borne diseases. Moreover, 28.5% of students had a history of food poisoning, whose knowledge and attitude levels were significantly less than those of students who had no history of food poisoning (P&le0.001). Conclusions: As the study findings revealed, training programs in the form of workshops and courses related to hygiene and food safety can be effective for the students in increasing students' knowledge especifically lower grades students. These programs should contain practical information about microbiology of transmitted diseases through food and proper food storage methods.